Citraan dan Diksi dalam Lirik Lagu Mahalini Album Fabula sebagai Bahan Ajar Menulis Puisi - Apriliany, Yeppi; Sabardila, Atiqa (Universitas Lampung, 2024)
The purpose of this research is to analyze the variations in imagery and diction found in the lyrics of Mahalini's album